HUBUNGAN SELF EFFICACY TERHADAP PENINGKATAN MOTIVASI BELAJAR DAN HASIL BELAJAR MATEMATIKA SISWA DI SEKOLAH - Abd Aziz Hsb (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2021)
Mathematics as one of the most important subjects in life, knowledge of mathematics is very supportive of every activity that occurs in everyday life, so mathematics is one of the most important subjects to be mastered by students at school, but in fact mathematics is a subject which students dislike so much that it has a negative impact on the quality of student learning outcomes in schools. low mathematics learning outcomes in schools can be caused by low desire, students' self-confidence in mastering mathematics lessons, low motivation in students to be one of the triggers for low learning outcomes achieved. Students' self-efficacy (self-confidence) and student learning motivation are believed to have a role in improving the quality of students' mathematics learning outcomes at school. Therefore, in this study, researchers examined the relationship between self-efficacy and increased learning motivation and student learning outcomes in mathematics at school. The research was conducted on students at Madrasah Tsanawiyah Negeri 13, South Jakarta, the research sample was 65 students, the data were collected using an instrument questionnaire and analyzed by correlation and regression analysis. From the results of the study, it was found that self-efficacy had a positive relationship to students' learning motivation and mathematics learning outcomes at school, as well as learning motivation to have a positive relationship to students' mathematics learning outcomes at school. Thus, in improving students' mathematics learning outcomes, it is necessary to emphasize supervision, attention and appropriate strategies to improve students' self-efficacy and student motivation.